A mathematical model for perforation of metal plates through adiabatic shear plugging. (May 2022) - Sen, Subhajit; Shaw, Amit; Nayak, Subrata
Highlights: Adiabatic shear plugging is a common perforation mechanism. A mathematical model for plugging failure in metal plates is developed. Final model is in the form of a set of ODEs. Developed model is validated through experiments and numerical results. Abstract: A mathematical model for perforation of metal plates by cylindrical projectiles through adiabatic shear plugging mechanism is developed. The proposed model takes into account some of the important attributes such as through-thickness wave propagation, spatial and temporal variation of field variables (velocity, strain and stress), elasto-plastic deformation at the impact zone, plastic shear localization, thermal softening and failure. The efficacy of the model is demonstrated by comparing the predicted responses (velocity time history, residual velocity of the projectile, ballistic limit or limit velocity of the target etc.) with the corresponding experimental and numerical observations. The present model, expressed in the form of a set of ODEs, provides a quick insight into the effect of various underlying parameters which may govern the plugging failure of metal plates. This may be useful for forming design provisions for impact-resistant structures.